Reinnervation of segmented latissimus dorsi muscle with the distal stump of the thoracodorsal nerve: A preliminary experimental study in rats. Issue 7 (3rd September 2013) - Kurita, Masakazu; Yamazaki, Kazunori; Eto, Hitomi; Seike, Shien; Takushima, Akihiko; Harii, Kiyonori
<x xml:space="preserve">Abstract</x> To date, nerve stumps have been dissected at the proximal side of the donor muscle for reinnervation of the muscle in free neurovascular muscle transfer. Herein, we examined the use of the distal thoracodorsal nerve, dissected from the muscle belly at the distal side of the latissimus dorsi muscle, for the reinnervation of muscle. The rat right latissimus dorsi muscle was employed as the model for our study. Twenty Wistar rats were used in this study. A rectangular muscle segment was dissected with the distal stump of dominant thoracodorsal nerve. After rotation of muscle, the distal nerve stump was sutured to a severed proximal recipient thoracodorsal nerve (n = 5). The degree of reinnervation through the distal nerve stump was compared with control groups that received proximal‐to‐proximal nerve sutures (n = 5), nerves that were not severed (n = 5), and severed nerves that were not sutured (n = 5) using electrophysiological, histological, and muscular volume assessments. Reinnervation of the distal nerve stump was confirmed by the contraction of the muscle following electrical stimulation and electromyography. Crossing of axons into motor endplates was confirmed by histology. Results of these assays were similar to that of the proximal nerve suture group. The volume of muscle in the distal nerve suture group was not significant different from that of the proximal nerve suture group (P = 0.63). It was demonstrated that the distal stump of the thoracodorsal nerve can be used to innervate segmented latissimus dorsi muscle. This novel procedure for the reinnervation of transplanted muscle deserves further investigations. © 2013 Wiley Periodicals, Inc. Microsurgery 33:545–550, 2013.